Intrahepatic Bile Duct Adenoma Mimetizing Metastatic Liver Disease in a Case of Colorectal Adenocarcinoma: A Case Report - Eller, Ana Alice Broering; Barg, Augusto Besen; Simas, Rafael; Lanzarin, Luciana Depiere; Ogata, Daniel Cury (Brazilian Journal of Case Reports, 2026)
Colorectal cancer (CRC) is a common malignant tumour of the large intestine or rectum, the incidence of which is rising worldwide, particularly in countries undergoing transition. Liver metastases are common in patients with CRC, occurring in up to 50% of cases, with the liver being the most frequent site of spread. Intrahepatic bile duct adenoma, a rare benign tumour, can mimic liver metastases in patients with CRC, and is often confused with adenocarcinomas due to histological and radiological similarities. Correct differentiation is essential to avoid unnecessary aggressive treatments. Based on the above, this project aims to study the case of a patient with a history of colorectal adenocarcinoma and an intrahepatic bile duct adenoma mimicking metastatic liver disease.